COMPETENCE APPROACH AS A METHODOLOGICAL LANDMARK OF MODERNIZATION OF MODERN EDUCATION - Palamar, Svetlana (Educological discourse, 2018)
Abstract. The author analyzes the procedural and substantive aspects of the competence approach as a methodological benchmark for the modernization of modern education; argues that the competence approach is directed at the educational results not as the sum of the acquired information, but as the ability of a person to act in different situations. Competence is studied in the context of the world pedagogical practice. The created competence of the student is characterized as the main qualitative indicator of the obtained education, hence, this achievement can be considered a pedagogical aim, which fully reflects the needs of society and individual. Using the point of view of didactic purposes, author emphasizes the need for changes in the content of education through the level of taught subject, used educational materials, and through the interaction of the teacher and the student. The formed competence of the student is a key indicator of the quality of the educational results. That is why the key competency structure should consist of the following components: motivational (positive cognitive setting of the student's personality, his / her relation to the educational activity, personal and social meaning, self-actualization); cognitive (readiness and success in acquiring knowledge, ways of activity, readiness and ability to receive information from different sources, self-esteem); operational activity (training - readiness to use the acquired knowledge and skills; readiness and ability to continue education at different levels; readiness for practical activity; use of learning outcomes in real life situations; mobility of knowledge and skills; experience of acting creatively); emotional (need to master knowledge, joy of cognition, activity, responsibility); experience in socialization (adaptation in a social environment, communicative, willingness to cooperate, independence); reflexive (self-analysis of the results, method of the received product, etc.). Prospects for further research are associated with the search for ways to solve the problem of the practical application of knowledge by students, because the modern labor market as a determinant of the development of socio-economic relations and the correlation factor of globalization processes requires education to include technologies and knowledge that meets the needs and challenges of the modern society. In this context, both the social components of knowledge and the processes of formation of key competencies are being relevant. Hence, this topic requires further comprehensive scientific analysis and justification.